Different effects of acute and chronic oxidative stress on the intestinal flora and gut-liver axis in weaned piglets - Zhang, Hongyu; Xiang, Xuan; Wang, Chenyu; Li, Tiejun; Xiao, Xuping; He, Liuqin (Frontiers in Microbiology, 2024)
Oxidative stress plays a pivotal role in modulating the balance of intestinal flora and the gut-liver axis, while also serving as a key determinant of the growth potential of weaned piglets. However, few studies have subdivided and compared acute and chronic oxidative stress. We constructed an intestinal model of acute oxidative stress in weaned piglets using paraquat (PQ) and a chronic oxidative stress model using D-galactosa to systematically compare their effects. Both acute and chronic oxidative stress models impaired intestinal barrier function and liver function. Chronic stress caused by D-galactose can result in severe redox dysregulation, while acute stress caused by paraquat can lead to inflammation and liver damage. Additionally, the components involved in the CAR pathway were expressed differently. Chronic or acute oxidative stress can reduce the diversity and composition of intestinal flora. In the PQ group, the richness of Mogibacterium and Denitratisoma improved, but in the D-gal group, the richness of Catenisphaera and Syntrophococcus increased. Not only does this research deepen our understanding of the effects of acute and chronic oxidative stress on intestinal functions, but it also characterizes characteristic changes in the gut flora, potentially identifying novel therapeutic targets and opening new avenues for future research.